EFFECTIVENESS OF ONLINE SKCK SERVICES TO INCREASE PUBLIC SATISFACTION BY SAINTELKAM POLRES BATANG - Rayhan Viko Paramanandana (Indonesian Journal of Police Studies, 2022)
ABSTRACT EFFECTIVENESS OF ONLINE SKCK SERVICES TO INCREASE PUBLIC SATISFACTION BY SAINTELKAM POLRES BATANG Rayhan Viko Paramanandana, 18.141, rayhanviko30@gmail.com The writing of this final project is based on an innovation related to the services of the Indonesian National Police to the community, this innovation is in the form of SKCK Online. But the issuance of SKCK Online is lower than manual SKCK. This is due to several inhibiting factors. Satintelkam personnel are not ready, facilities and infrastructure are damaged, methods are still not perfect, and the public is not aware of the existence of SKCK Online. Therefore, a study was conducted that aims to find out how effective the SKCK Online service is at the Batang Polres, and how to make the SKCK Online service effective at the Batang Polres. This study uses the theory of effectiveness, the concept of public service, and the concept of online SKCK and management theory as an analytical knife. This approach uses a qualitative approach with the type of descriptive research. The data sources used are primary data sources in the form of interviews, and secondary data sources in the form of documents, as well as research related to this research. Data collection techniques in this study used observation, interviews and document review. The data analysis techniques used are data collection, data reduction, data presentation and conclusion drawing Research conducted at the Batang Polres resulted in a finding, namely Online SKCK which aims to make it easier for applicants and officers to make SKCK, but the number of online SKCK applicants at the Batang Polres is still less compared to manual SKCK. The inhibiting factors in carrying out these services are caused by internal factors in the form of a lack of Satintelkam personnel who conduct SKCK Online training, SKCK Online service equipment is not optimal. And the method of issuing SKCK Online still has to come to the Batang Polres for fingerprint recording and SKCK taking. External factors come from the community itself. With this, the Batang Intelkam Unit has not been able to provide services in accordance with the concept of public service. The author's suggestion in this study is to eliminate the inhibiting factors for online SKCK services and increase the socialization carried out to the Batang community so that people use online SKCK. Keywords: Effectiveness, Service, Online SKCK, Public Service, Batang Police Intelligence Unit